Implementasi Kebijakan Pembayaran Kapitasi Berbasis Kinerja (KBK) di Puskesmas Kabupaten Nganjuk - Christyana Sandra; Solikha Tri Cahyati; Yennike Tri Herawati (Jurnal Kebijakan Kesehatan Indonesia, 2023)
KBK has a role as one of the quality control efforts to control costs in FKTP, based on the results of a preliminary study at the Nganjuk District Health Office, it is known that there are 5 Primary Health Care in Nganjuk District that cannot meet the indicators in the KBK so that the capitation received is not 100% full during 2018-2021. This study aims to describe how the KBK payment policy is implemented based on standard variables and policy objectives, resources, communication, and social conditions. This was a qualitative study. Results showed that the standards and objectives of the KBK payment policy are well understood, but the RPPT standards have been difficult to meet so far. Based on the aspect of facility resources, puskesmas are still often constrained by the information system used for data input. Communication in implementing policies has been going well starting from the process of distributing information, clarity of information, and consistency of information. The social conditions of the community around the puskesmas, especially the type of work and age, also influence the achievement of the contact number target at the puskesmas. The KBK payment policy has been implemented, but it is necessary to evaluate the policy so that further improvements and policy developments can be carried out.